Impact of type 2 diabetes on postoperative outcomes after endovascular aortic aneurysm repair – a cohort study - António Duarte; Hugo Fabian Gonçalves; Ryan Gouveia e Melo; Pedro Amorim; Ruy Fernandes e Fernandes; Luís Mendes Pedro (Angiologia e Cirurgia Vascular)
INTRODUCTION: Although the incidence of abdominal aortic aneurysms (AAA) has declined over the last two decades, this condition has high mortality rates when symptomatic or ruptured. Paradoxically, diabetes seems to slow AAA progression or rupture. However, there is little and contradictory data regarding the postoperative setting. This study aims to evaluate the clinical impact of diabetes after standard EVAR.